Integration of Digital Media in the Discovery Learning Model to Enhance Junior High School Students Conceptual Understanding in Science: A Review - Kinanthi Asta Maharani; Siti Shofa Assyifaul Qulbi Barid; Sri Rejeki Dwi Astuti; Sri Wahyuni (Jurnal Pijar MIPA, 2026)
The low level of students' conceptual understanding in science learning remains a primary issue, as instructional activities often emphasize rote memorization and fail to optimally utilize digital media to support meaningful learning. This study aims to examine the role of digital media across the stages of the Discovery Learning model, identify the most effective types of digital media, and determine the characteristics of science topics that require technological support. The research method employed is a Systematic Literature Review (SLR) of 15 relevant articles published between 2020 and 2025. Data were analyzed thematically by grouping findings based on the role of digital media in the Discovery Learning stages, media types, science topics, as well as supporting and inhibiting factors in implementation. The results indicate that digital media such as PhET simulations, animated videos, interactive flipbooks, and augmented reality significantly enhance students' conceptual understanding by providing visual and interactive representations. These media are most effective for abstract topics such as energy, the solar system, and the digestive system. However, their implementation faces challenges, including limited school facilities, low digital literacy among teachers and students, and insufficient preparation time. The integration of digital media within the Discovery Learning model proves effective in concretizing abstract science concepts, with the novelty of this study lying in its comprehensive mapping of the relationships between media types, learning stages, and topic characteristics. Practically, these findings can serve as a guide for educators in selecting and designing digital media for more innovative instruction. Academically, this study encourages further research to address implementation challenges and to explore more personalized and adaptive technology integration for supporting quality science education.